2019
DOI: 10.1016/j.quaint.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Holocene landscape dynamics in the Ghaggar-Hakra palaeochannel region at the northern edge of the Thar Desert, northwest India

Abstract: Precession-forced change in insolation has driven de-intensification of the Asian Monsoon systems during the Holocene. Set against this backdrop of a weakening monsoon, Indus Civilisation populations occupied a number of urban settlements on the Ghaggar-Hakra plains during the mid-Holocene from 4.5 ka until they were abandoned by around 3.9 ka. Regional climatic variability has long been cited as a potential factor in the transformation of Indus society, however there remain substantial gaps in the chronologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…6c; Dixit et al, 2014). The flood regime controlled by this variable and declining summer monsoon became more erratic and/or spatially restricted Durcan et al, 2017) making inundation agriculture less dependable. Whether fast or over generations, the bulk of Harappan settlements relocated toward the Himalayan foothills on the plains of the upper G-H interfluve (see Supplement; Possehl, 2002;Kenoyer, 1998;Wright, 2010;Madella and Fuller, 2006;.…”
Section: Climate Instability and The Harappan Metamorphosismentioning
confidence: 99%
“…6c; Dixit et al, 2014). The flood regime controlled by this variable and declining summer monsoon became more erratic and/or spatially restricted Durcan et al, 2017) making inundation agriculture less dependable. Whether fast or over generations, the bulk of Harappan settlements relocated toward the Himalayan foothills on the plains of the upper G-H interfluve (see Supplement; Possehl, 2002;Kenoyer, 1998;Wright, 2010;Madella and Fuller, 2006;.…”
Section: Climate Instability and The Harappan Metamorphosismentioning
confidence: 99%
“…f), has also been cited as the cause of the abrupt collapse of the Egyptian Old Kingdom at the same time (Thompson et al ., ; Bronk Ramsey et al ., ; Walker et al ., , ). Nearer Dholavira, sedimentological evidence from the Thar Desert suggests westward expansion of the desert dune field during the Late Holocene (after ~4000 years BP ) overlying the older fluvial sediments that were deposited during the Holocene climate optimum (Clift et al ., ; Alizai et al ., ; Giosan et al ., ; East et al ., ; Durcan et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…1900 years Before Christ). Although, dune formation in the Thar desert is a long process spanning at least 200 ka BP [56], some recent dating of dunes from the northernmost edge of the Thar desert, have suggested that dune deposits pre-date 4.9 ka BP, though some are around 1500 years old ( [27] (p. 4), [58][59][60]). Therefore, it seems logical to expect a long period of dune formation and interaction with rivers before the latter were finally erased.…”
Section: Discussionmentioning
confidence: 99%